Protective effects of glycycoumarin and procyanidin B1, active components of traditional Japanese medicine yokukansan, on amyloid β oligomer-induced neuronal death. (15th January 2015) - Kanno, Hitomi; Kawakami, Zenji; Tabuchi, Masahiro; Mizoguchi, Kazushige; Ikarashi, Yasushi; Kase, Yoshio
Abstract: Ethnopharmacological relevance: Yokukansan, a traditional Japanese (Kampo) medicine, is composed of seven medicinal herbs, and has been traditionally used to treat neurosis, insomnia, and night crying and irritability in children. Yokukansan and its constituent herbs, Glycyrrhiza and Uncaria Hook, have recently been shown to have protective effects against amyloid β (Aβ) oligomer-induced apoptosis by suppressing the activation of caspase-3 in primary cultured neurons. The aim of the present study was to identify the effective components of Glycyrrhiza and Uncaria Hook against Aβ oligomer-induced neurotoxicity. We also attempted to clarify the mechanisms by which yokukansan and these herbs, as well as their components, suppressed the activation of caspase-3 in Aβ oligomer-treated neurons. Materials and methods: Rat primary cultured cortical neurons were treated with Aβ oligomer (3 μM). The protective effects of 16 components derived from Glycyrrhiza or Uncaria Hook against Aβ oligomer-induced neurotoxicity were determined using the MTT reduction assay 48 h after the treatment. The suppressive effects of the test substances, i.e., yokukansan, Glycyrrhiza, Uncaria Hook, and screened components, on the Aβ oligomer-induced activation of caspase-3(/7) were evaluated using the caspase-Glo assay 48 h after the Aβ oligomer treatment. The suppressive effects of the test substances on the activation of caspase-8 and -9, both of which are located upstream of caspase-3, were also examined 24 h after the Aβ oligomer treatment. Results: Two of the 16 components tested, glycycoumarin derived from Glycyrrhiza and procyanidin B1 derived from Uncaria Hook, significantly inhibited Aβ oligomer-induced neuronal death in a dose-dependent manner. Glycyrrhiza, Uncaria Hook, and yokukansan significantly suppressed the Aβ oligomer-induced activation of caspase-3 as well as caspase-8 and -9. Glycycoumarin also suppressed the activation of caspase-3, but not caspase-8 and -9. Procyanidin B1 suppressed the activation of caspase-3, -8, and -9. Conclusions: Our results demonstrated that glycycoumarin and procyanidin B1 had ameliorative effects on Aβ oligomer-induced neurotoxicity. The neuroprotective effects of glycycoumarin are thought to be due to the attenuated activation of caspase-3, but not caspase-8 or -9. Procyanidin B1, as well as yokukansan, Glycyrrhiza, and Uncaria Hook, may attenuate the activation of caspase-3 by inhibiting that of caspase-8 and -9. Graphical abstract: